2001
DOI: 10.1097/00007890-200102270-00009
|View full text |Cite
|
Sign up to set email alerts
|

FasL IS IMPORTANT IN COSTIMULATION BLOCKADE-RESISTANT SKIN GRAFT REJECTION

Abstract: FasL is not required for the establishment of costimulation blockade induced hyporesponsiveness, but rather appears to be required for normal costimulation blockade resistant rejection. Fas expression is not critical for costimulation blockade resistant rejection, suggesting that fasL may be interacting with other receptors. Further, it appears that CD4+ cells are important in the maintenance of allograft protection induced by costimulation blockade in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
1
5
2
Order By: Relevance
“…Although the Fas–FasL pathway plays a vital role in mediating the process of activation‐induced cell death, previous studies in lpr and gld mice and our findings (Fig. ) suggest that the Fas–FasL apoptotic pathway is not crucial for the deletion of alloreactive T cells during tolerance induction.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Although the Fas–FasL pathway plays a vital role in mediating the process of activation‐induced cell death, previous studies in lpr and gld mice and our findings (Fig. ) suggest that the Fas–FasL apoptotic pathway is not crucial for the deletion of alloreactive T cells during tolerance induction.…”
Section: Discussioncontrasting
confidence: 59%
“…These findings suggest that alloreactive T cells prevented from undergoing deletion during co-stimulation blockade by exposure to inflammation remain susceptible to apoptotic stimuli. Although the Fas-FasL pathway plays a vital role in mediating the process of activation-induced cell death, previous studies in lpr and gld mice [35][36][37] and our findings ( Fig. 4) suggest that the Fas-FasL apoptotic pathway is not crucial for the deletion of alloreactive T cells during tolerance induction.…”
Section: Discussioncontrasting
confidence: 57%
“…This has been supported by recent studies in which a Fas-Fc-receptor construct or specific caspace inhibitors blocked T-cell co-stimulation (30). In an allograft model we have found that combined blockade of the CD28 and CD40 pathways resulted in prolonged allograft survival in FasL-deficient mice compared with wild-type mice (31). These data suggest that manipulation of the Fas pathway may be a useful component of strategies that promote the acceptance of transplanted organs.…”
Section: Fas and Fas Ligandsupporting
confidence: 63%
“…Although a complete review of the known effects of TNFR/TNF superfamily members in the development and regulation of the immune system is beyond the scope of this article, interested readers are referred to two recent reviews (8,9). Members of the TNFR superfamily are defined by the homology of their extracellular domains particularly with respect to a specific repetitive pattern of cys- Table 1: Summary of reviewed TNFR superfamily molecules and their ligands Receptor Distribution Ligand TNF Distribution Properties TNFR superfamily superfamily (references pertaining to transplantation) FAS (CD95, T and B cells, APC, FASL T cells, APC, and Involved in peripheral T-cell homeostasis via APO-1) and stromal cells (TNFSF6) stromal cells 'fratricide', may deliver co-stimulatory signal (TNFRSF6) (27,28,31) teine residues. The cytoplasmic region of TNFR superfamily members can be categorized by the presence or absence of a death domain that, upon engagement of the receptor by the appropriate ligand, can induce apoptosis (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The integrity of activation induced cell death (AICD) and passive cell death (PCD) pathways is critical for allograft tolerance with treatments that do not permanently or totally eradicate donor reactive effector T cells, such as costimulation blockade (17–19). The widely used immunosuppressive drug cyclosporine interferes with AICD of effector T cells (19–21) and is detrimental to tolerance induction when used as an adjunct to a costimulation blockade based regimen (17,18,22). However, in our previous studies, the impact of cyclosporine on T regs has not been investigated.…”
Section: Introductionmentioning
confidence: 99%